Effect of polyvinylidene fluoride on the fracture microstructure characteristics and piezoelectric and mechanical properties of 0-3 barium zirconate titanate ceramic-cement composites - Thanyapon Wittinanon (2020)
© 2020 Elsevier Ltd Barium zirconate titanate (40−60 vol.%; BZT), Portland cement (PC) and polyvinylidene fluoride (0−7 vol.%; PVDF) were used as raw materials to produce 0–3 piezoelectric cement-based composites. The highest piezoelectric charge coefficient (d33∼26-27 pC/N) was found at 50−60 vol.% BZT with 5 vol.% PVDF. Moreover, the composite with 50 vol.% BZT and 5 vol.% PVDF had the highest piezoelectric voltage coefficient (g33 = 16.0 × 10−3 V·m/N). Scanning electron microscopy was used to investigate the morphology of the fracture surface of the composite. When PVDF was used in the composite, it was observed to fill some pores at the interface zone and within the cement phase. The elastic behaviour of PVDF could also be seen in the fracture surface, where it appeared as a stretched material different from both the BZT ceramic and cement, which are brittle materials. In addition, increasing the PVDF content led to increased fracture toughness.